2005
DOI: 10.3171/jns.2005.102.2.0209
|View full text |Cite
|
Sign up to set email alerts
|

Resection of brain metastases previously treated with stereotactic radiosurgery

Abstract: Sixty-one patients (each harboring three or fewer brain lesions), who were treated at a single institution between June 1993 and August 2002 were identified. Patient charts and their neuroimaging and pathological reports were retrospectively reviewed to determine overall survival rates, surgical complications, and recurrence rates. A univariate analysis revealed that patient preoperative recursive partitioning analysis (RPA) classification, primary disease status, preoperative Karnofsky Performance Scale score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 28 publications
(19 reference statements)
2
42
0
Order By: Relevance
“…In single metastasis, PRS has been introduced as an alternative treatment option (17), although treatment of tumors with irregular borders or localization in less accessible intracranial regions still requires external stereotactic radiosurgery with Linac or Gamma Knife (5,33). Patients with large tumors and distinct edema benefit from surgery, combined with WBRT, which offers quickly recovery of neurological symptoms, leading to a lower consumption of steroids (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In single metastasis, PRS has been introduced as an alternative treatment option (17), although treatment of tumors with irregular borders or localization in less accessible intracranial regions still requires external stereotactic radiosurgery with Linac or Gamma Knife (5,33). Patients with large tumors and distinct edema benefit from surgery, combined with WBRT, which offers quickly recovery of neurological symptoms, leading to a lower consumption of steroids (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Another series of 45 patients receiving one or more courses of salvage SRS for new lesions after initial management with SRS plus or minus WBRT found one year local control of 92%, while the median survival was 6.5 months [14]. Surgical resection of 1-3 recurrent or progressive metastases initially treated with SRS has also been described in a series of 61 patients, as an alterative to WBRT [143]. The median survival after salvage surgery was 11 months.…”
Section: Management Of Recurrent Brain Metastasesmentioning
confidence: 95%
“…In patients with recurrence, MST after the second surgery is reportedly 11.5 months, 19 whereas MST after surgery in patients with recurrence after gamma knife radiosurgery is 11.1 months. 20 In a study reported before 1990, when additional gamma knife treatment was not available, patients with recurrences after WBRT at 30 Gy received another WBRT at 25 Gy. Therapeutic effi cacy was achieved in 42% of these patients, and MST was 5 months, although there was no detailed discussion of safety.…”
Section: Recurrence After Surgery and Radiotherapymentioning
confidence: 99%
“…However, additional stereotactic irradiation was actually performed in 9 and 19 patients, respectively; salvage therapy could not be conducted in all patients with tumor recurrence. The mean memory test score (maximum score, 30 points) on the mini-mental state examination (MMSE) in patients who survived for more than 1 year was 27.0 (range, [23][24][25][26][27][28][29][30] in the combined group and 28.0 (range, [18][19][20][21][22][23][24][25][26][27][28][29][30] in the SRS-alone group, showing no signifi cant difference between the two groups. Thus, SRS combined with WBRT did not increase the incidence of dementia as compared with SRS alone.…”
Section: Radiotherapy For Patients Not Suitable For Surgerymentioning
confidence: 99%